The Structure and Behavioral Effects of Revealed Social Identity Preferences*. Issue 632 (21st May 2020) - Hett, Florian; Mechtel, Mario; Kröll, Markus
Abstract: A large body of evidence shows that social identity affects behaviour. However, our understanding of the substantial variation of these behavioural effects is still limited. We use a novel laboratory experiment to measure differences in preferences for social identities as a potential source of behavioural heterogeneity. Facing a trade-off between monetary payments and belonging to different groups, individuals are willing to forego significant earnings to avoid belonging to certain groups. We then show that individual differences in these foregone earnings correspond to the differences in discriminatory behaviour towards these groups. Our results illustrate the importance of considering individual heterogeneity to fully understand the behavioural effects of social identity.